2014
DOI: 10.1186/1824-7288-40-28
|View full text |Cite
|
Sign up to set email alerts
|

Childhood intussusceptions at a tertiary care hospital in northwestern Tanzania: a diagnostic and therapeutic challenge in resource-limited setting

Abstract: Background: Intussusception remains a common cause of bowel obstruction in children and results in significant morbidity and mortality if not promptly treated. There is a paucity of prospective studies regarding childhood intussusception in Tanzania and particularly the study area. This study describes the pattern, clinical presentations and management outcomes of childhood intussusception in our setting and highlights the challenging problems in the management of this disease. Methods: This was a prospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
67
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(93 citation statements)
references
References 36 publications
24
67
2
Order By: Relevance
“…Similar to other studies from developing countries, most of the cases of intussusception in this series were managed surgically [1, 2, 5, 812]. The predominant operative management is due to delayed patient presentation with concern for gangrenous bowel, predominant clinical diagnosis, with a significant proportion of cases being confirmed at laparotomy and lack of around-the-clock radiologic facilities and personnel to perform nonsurgical reduction [2, 11, 12]. This argument is underscored in this series where the median durationof presentation was 3 days, with gangrenous bowel noted in 62.1% of the cases.…”
Section: Discussionsupporting
confidence: 79%
“…Similar to other studies from developing countries, most of the cases of intussusception in this series were managed surgically [1, 2, 5, 812]. The predominant operative management is due to delayed patient presentation with concern for gangrenous bowel, predominant clinical diagnosis, with a significant proportion of cases being confirmed at laparotomy and lack of around-the-clock radiologic facilities and personnel to perform nonsurgical reduction [2, 11, 12]. This argument is underscored in this series where the median durationof presentation was 3 days, with gangrenous bowel noted in 62.1% of the cases.…”
Section: Discussionsupporting
confidence: 79%
“…However, Ameh reported a longer duration of hospital stay in his patients. In their study of childhood intussusception, Chalya et al reported that the length of hospital stay was longer in children who had intestinal resection when compared with those who had no resection [11] . In the current study, intussusception was the most common indication for intestinal resection.…”
Section: Discussionmentioning
confidence: 99%
“…Red current Jelly stool was present in 53% patients. However, palpable lump and rigidity/guarding were present only in 10% and 08% patients [8] .…”
Section: -Age Incidencementioning
confidence: 99%
“…In study conducted by Chalya and Kaynge et. al., Ileo colic intussusception was common, present in almost 67.9% patients, followed by colo colic present in 25% patients [8] . In study conducted by Hazra and Karki et.…”
Section: -Types Of Intussusceptionmentioning
confidence: 99%
See 1 more Smart Citation